KOMUNIKASI PSIKIATER DAN PASIEN PENDERITA BIPOLAR - Merizha Yamudaha; Femi Oktaviani; Reza Rizkina Taufik (J-IKA, 2015)
ABSTRACTInterpersonal communication is a communication made between two people, where there is direct contact either verbal or nonverbal, and has effectiveness in changing attitudes, opinions or behavior because it possesses a dialog where backflow occurs directly, as is the case for psychiatrists and patients with bipolar disorder. Issues to be discussed, namely 1. What forms of interpersonal communication that do psychiatrists and patients with bipolar disorder in the recovery process 2. What factors interpersonal communication helps the recovery process of patients with bipolar disorder 3. Why do psychiatrists proximity to the recovery process of patients with disorders bipolar 4. What obstacles encountered psychiatrist when communicating with patients with bipolar disorder in the recovery process. This problem is very important investigation, to determine interpersonal communication easier for psychiatrists to interact with patients with bipolar in the recovery process. The research method that researchers use the method of qualitative case study approach, and the paradigm used by researchers is critical paradigm. Where researchers are also collecting data through observation, interviews directly to the informant, documentation, and literature study. In this case, the results of research to researchers conclude that interpersonal communication that do psychiatrists and patients with bipolar greatly help facilitate the psychiatrist to interact with the patient in the recovery process, where the psychiatrist and the family is the central figure who took part in the recovery process.Keywords: Interpersonal Communication, Psychiatrists, Bipolar Patients ABSTRAKKomunikasi antarpribadi merupakan komunikasi yang dilakukan antara dua orang, dimana terjadi kontak langsung baik secara verbal ataupun nonverbal, serta memiliki keefektifan dalam merubah sikap, pendapat atau perilaku seseorang karena memiliki sifat dialogis dimana arus balik terjadi secara langsung, sama halnya yang terjadi pada psikiater dan pasien penderita gangguan bipolar.  Permasalahan yang akan dibahas, yaitu 1. Bagaimana bentuk komunikasi antarpribadi yang dilakukan psikiater dan pasien penderita gangguan bipolar pada proses pemulihan 2. Bagaimana faktor-faktor komunikasi antarpribadi membantu proses pemulihan pasien penderita gangguan bipolar 3. Mengapa psikiater melakukan kedekatan pada proses pemulihan pasien penderita gangguan bipolar 4. Bagaimana hambatan-hambatan yang ditemui psikiater saat berkomunikasi dengan pasien penderita gangguan bipolar pada proses pemulihan. Permasalahan ini sangatlah penting diteliti, untuk mengetahui komunikasi antarpribadi memudahkan psikiater berinteraksi dengan pasien penderita bipolar pada proses pemulihan. Metode penelitian yang peneliti gunakan yaitu metode kualitatif dengan pendekatan studi kasus, dan paradigma yang digunakan oleh peneliti yaitu paradigma kritis. Dimana peneliti juga melakukan pengumpulan data melalui observasi, wawancara secara langsung kepada informan, dokumentasi, dan studi kepustakaan. Dalam hal ini, hasil dari penelitian yang dapat peneliti simpulkan bahwa komunikasi antarpribadi yang dilakukan psikiater dan pasien penderita bipolar sangat membantu  memudahkan psikiater untuk berinteraksi dengan pasien pada proses pemulihan, dimana psikiater dan keluarga adalah tokoh sentral yang ikut andil dalam proses pemulihan.Kata Kunci: Komunikasi Antarpribadi, Psikiater, Pasien Bipolar